Capital humano y su incidencia en el crecimiento económico, un análisis global y por niveles de desarrollo utilizando técnicas de cointegración y corrección de error, período 1980-2016 - Armijos Chamba, Jessica Jackeline (2018)
Human capital is identified as one of the main determinants of economic growth, education and qualification of the population are the main assets and a necessary condition to compete in the global market. An increase in the capacities of workers translates into an increase in total production, implying an improvement in efficiency and therefore greater growth of the economies. That is why the research entitled "Human capital and its impact on economic growth, a global analysis and income levels using cointegration techniques and error correction, period 1980-2016" was carried out. Whose general objective was: To examine the incidence of human capital globally and by levels of development in the period 1980-2016, by means of a descriptive and econometric study, using cointegration techniques and error correction, with data in a panel, with the purpose to establish the effect on economic growth. The study had a global approach, for 81 economies considering the productive structure of the countries, that is, the economies were grouped by High Income Countries (HIC), High Average Income Countries (HAIC), Middle Income Countries Low (MICL) and finally the Low Income Countries (LIC). It was done through the management of historical data from official sources, databases of the World Bank (2017) and Barro and Lee (2013). It was found that human capital has a stable short-term relationship in the economic growth of countries, however this relationship does not exist in the long term, that is, an increase in education would lead to an increase in growth in the short term However, increases in the accumulation of human capital will not affect in the long term if there is no favorable scenario for human capital to have an effect on growth